2015
DOI: 10.1002/stem.2189
|View full text |Cite
|
Sign up to set email alerts
|

TIMP3 Attenuates the Loss of Neural Stem Cells, Mature Neurons and Neurocognitive Dysfunction in Traumatic Brain Injury

Abstract: Mesenchymal stem cells (MSCs) have been shown to have potent therapeutic effects in a number of disorders including traumatic brain injury (TBI). However, the molecular mechanism(s) underlying these protective effects are largely unknown. Herein we demonstrate that tissue inhibitor of matrix metalloproteinase-3 (TIMP3), a soluble protein released by MSCs, is neuroprotective and enhances neuronal survival and neurite outgrowth in vitro. In vivo in a murine model of TBI, intravenous recombinant TIMP3 enhances de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 63 publications
4
37
0
Order By: Relevance
“…There are similarities between MAPC and MSC but there do not appear to be any rigorous comparisons of the two cell types that identify their differences . Interestingly, when MSC are administered intravenously, they are initially trapped in the pulmonary circulation through a first pass effect for several hours and the beneficial effects on the injured brain occurs through release of paracrine factors, such as TSG‐6 and TIMP‐3 and HGF, rather than direct migration and differentiation of the MSC to the brain . The potential role of microvesicles released by MSC has also been studied in experimental models of TBI, and demonstrated that microvesicles and exosomes may well also play a role in reducing experimental brain injury .…”
Section: Multiple Organ Failure Following Traumamentioning
confidence: 99%
“…There are similarities between MAPC and MSC but there do not appear to be any rigorous comparisons of the two cell types that identify their differences . Interestingly, when MSC are administered intravenously, they are initially trapped in the pulmonary circulation through a first pass effect for several hours and the beneficial effects on the injured brain occurs through release of paracrine factors, such as TSG‐6 and TIMP‐3 and HGF, rather than direct migration and differentiation of the MSC to the brain . The potential role of microvesicles released by MSC has also been studied in experimental models of TBI, and demonstrated that microvesicles and exosomes may well also play a role in reducing experimental brain injury .…”
Section: Multiple Organ Failure Following Traumamentioning
confidence: 99%
“…To that end some investigators are working with modified progenitor cells that are being reprogrammed to over-express certain factors secreted by progenitor cells, and some groups are directly injecting the factors themselves (such as TIMP3 or Wnt3a) (74, 76). As this research progresses the mechanism or mechanisms of action will be more fully understood, and cellular therapies can be better harnessed and used to the best benefit.…”
Section: Future Directionsmentioning
confidence: 99%
“…Studies have shown that both mature neurons and newborn neurons are vulnerable to TBI. Up to 80% of doublecortin‐positive (DCX+) neural stem cells are lost following moderate‐to‐severe TBI . In addition, newly generated neurons from hippocampal neurogenesis are thought to play critical roles in certain types of learning and memory .…”
Section: Introductionmentioning
confidence: 99%